2012
DOI: 10.1504/ijiscm.2012.051152
|View full text |Cite
|
Sign up to set email alerts
|

Delivering financial services through mobile phone technology: a pilot study on impact of mobile money service on micro-entrepreneurs in rural Cambodia

Abstract: Mobile technologies are powering up economic and social development in developing countries. This pilot study aims to generate a set of preliminary results that will contribute to advancing research on the impact of mobile money services on microenterprises and microentrepreneurs. The location of the study is set in rural Cambodia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 14 publications
1
9
0
2
Order By: Relevance
“…This is possible if everyone has access to secured saving accounts serviced through technologyenabled retail networks, and connected to the national payment systems including households, government and commercial providers. Vong et al, (2012) identified that micro-entrepreneurs who use mobile banking services in rural areas would benefit positively from the use of it in terms of time, security and convenience.…”
Section: Contribution Of Mobile Banking Service Towards Youth In Busimentioning
confidence: 99%
“…This is possible if everyone has access to secured saving accounts serviced through technologyenabled retail networks, and connected to the national payment systems including households, government and commercial providers. Vong et al, (2012) identified that micro-entrepreneurs who use mobile banking services in rural areas would benefit positively from the use of it in terms of time, security and convenience.…”
Section: Contribution Of Mobile Banking Service Towards Youth In Busimentioning
confidence: 99%
“…Studies in this domain examine the potentiality (Duncombe, 2012;Vong et al, 2012) and adoption (Etim, 2013) of mobile financing. According to Duncombe (2012), simple market modelling that depicts 'informal and formal' social networks or 'banked or unbanked' population is inadequate to assess m-finance potential.…”
Section: Mobile Financementioning
confidence: 99%
“…As such, m-finance must be re-examined in accordance with contextual analysis to include user experiences and environment. Vong et al (2012) illustrated that mobile money services are gaining traction and acceptance when used for daily business life in rural Cambodia. Mobile money services complemented or enhanced access to financial services that helped improve rural Cambodian livelihoods as well as micro or small businesses in terms of reduced operational costs, higher profit margin and higher market access opportunities.…”
Section: Mobile Financementioning
confidence: 99%
“…They need to create a women friendly environment by creating an aesthetic appeal, personalizing conversations, and fulfilling their unstated needs in an efficient manner. According to a pilot study conducted in Cambodia, it was observed that the impact on introduction of mobile banking has created social inclusion among the rural population in four major dimensions: consumption behaviour, participation in economy, political contribution and social network creations (Vong et al 2012). …”
Section: Micro Financial Products Designmentioning
confidence: 99%